Cortical O 2 supply and metabolism are suppressed in the aged mice - Hongyi Kang; Sitong Zhou; Michael Giannetto; Evan D. McConnell; Ning Kang; Qian Sun; Hetince Zhao; Helen S. Wei; Kevin Kramer; Yaojun Guo; Juliana S. Costa; Saul A. Villeda; et al. (Proceedings of the National Academy of Sciences, 2026)
Current evidence suggests that the rejuvenating effects of parabiosis on brain function arise from the exchange of blood factors that enhance synaptic plasticity, promote neurogenesis, and reduce neuroinflammation in aged animals. However, aging is also associated with diminished tissue oxygenation. Here, we report that erythrocytes (red blood cells, RBCs) from aged mice exhibit reduced responsiveness to low oxygen tension (PO 2 ) and release O 2 slower than those from young mice. In vivo, sensory stimulation evoked a smaller and delayed capillary RBC flow in aged mice. Although activity-evoked PO 2 dips were diminished in aged mice; experimentally reducing PO 2 to comparable levels did not restore capillary flow in aged mice, consistent with diminished RBC O 2 responsiveness observed ex vivo. Notably, RBCs from aged mice in heterochronic parabiosis pairs (young-aged) displayed faster responses to low PO 2 compared to those from aged mice in isochronic pairs (aged-aged). Together, these findings across multiple levels of analysis demonstrate that aging impairs RBC responsiveness to O 2 and suggest that improved RBC-mediated O 2 delivery contributes to the rejuvenating effects of parabiosis.